(untitled) (Research, Society and Development, 2021)
This paper presents a part of an investigation which aims to analyze the digital inclusion of young residents of Natal, a city in the State of Rio Grande do Norte (RN), Brazil. A quantitative, exploratory and descriptive pilot research was conducted with twenty-one young people, aged between 15 and 18 years old. The data were organized with the support of descriptive and inferential statistics. SPSS, Minitab and R software were used to calculate averages, standard deviations and perform Cluster Analysis. The results show that they have access to the Internet at home, through wi-fi and, principally, mobile network connections. The smartphone has revealed itself as the main access device (90%). About 66% use the Internet to access social networks and messaging applications and 47% to study. As for digital literacy, the results show satisfactory averages related to computer programming. However, they also show some difficulties related to (1) editing and content creation, (2) security and communication, (3) and research skills. This research offers indications for the debate about the digital inclusion of young people in vulnerability, living in peripheral communities of the aforementioned municipality.